Kuat Lekat Beton dengan Variasi Umur Beton, Kekasaran Permukaan, Kelembapan dan Mutu Beton - Andhini, Vania Meutia; Noorhidana, Vera Agustriana; Alami, Fikri (Universitas Lampung, 2020)
AbstractStructure strengthening by adding fresh concrete mix to he existing concrete has a weakness in the bonding between the concrete joint. Research on the concrete-to-concrete bond strength has been carried out with various treatments. This study aims to determine the factors that influence bond strength between old concrete (substrate) and new concrete (overlay). The factors include are the substrate's ages, substrate surface's roughness, water content of the substrate and the compressive strength of the added concrete.The test method used in this study is slant shear test to quantify the bond strength. 150 × 150 × 300 mm2 prism with the interface line angle at 30°to the vertical was used as the specimen. The specimen cast in 2 phases, first substrate casting and second overlay casting. The overlay cast at different age of substrate depends on the variation needed. The treatments given are: 1) difference of overlay compressive strength which use 15 MPa, 25 MPa and 45 MPa concrete compressive strength; 2) difference of substrate’s ages at 7 days, 28 days and 42 days; 3) difference of substrate surface’s roughness with 3 sub-variations smooth, medium and coarse; 4) difference of water content of substrate specimen with dry, SSD and wet sub-variations.Keyword : concrete-to-concrete bond strength, slant shear test, interface roughness, substrate's ages.